PERCUTANEOUS TRANSLUMINAL ANGIOPLASTY IN SUBCLAVIAN VEIN STENOSIS CAUSED BY CENTRAL VENOUS CATHETERIZATION FOR HEMODIALYSIS ACCESS IN CHRONIC KIDNEY DISEASE PATIENTS - Laksono, Gerardo; Motulo, Yosis Y; Tahalele, Paul L (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Introduction: The increased of central vein access for hemodialysis in chronic kidney disease patients has led to increase of side effect in clinically relevant stenosis of subclavian vein. One of therapeutic options to solve stenosis of subclavian vein is endovascular treatment Percutaneous Transluminal Angioplasty (PTA) .Objectives: To show our experience in treating subclavian vein stenosis using Endovacular treatment Percutaneous Transluminal Angioplasty (PTA). Materials and Methods: A retrospective study in 62 chronic kidney disease patients who undergo hemodyalisis with stenosis of subclavian vein treated with PTA in 3 hospitals in Surabaya from October 2017-October 2020 with range age 18-70 years was conducted .Results: We performed PTA for subclavian vein stenosis in 62 cases. Partial stenosis was found in 35 cases and total occlusion in 27 cases. For 27 total occlusion cases, 19 cases can still be opened, but 8 cases can’t be opened or recanalization and we drop out these patient. 54 cases (87%) were good and 8 cases (13%) can’t be open. The result of PTA in treating stenosis of subclavian vein was good. The result of reduced in arm swelling and using doppler USG follow up are 100%(54/54) after 1 month, 100%(54/54) after 3 months, 90.7% (49/54) after 6 months.Conclusion: Percutaneous Transluminal Angioplasty (PTA) is effective in treating subclavian vein stenosis reliefe its symptomps. The patency rate is 90.7% after 6 months post procedure of PTA.